Research of influence of working conditions on the general incidence of foundrymen - A. M. Lazarenkov (Литьë и металлургия)
Working conditions of workers in foundries and their influence on morbidity with temporary disability are considered. The results of the distribution of diseases in the foundry shops with different character of production for individual nosological forms. It is noted that the increased levels of noise and vibration, high dust concentration in the air of the working area, significant values of air temperature, the intensity of infrared radiation increase the number of cases of morbidity with temporary disability, such as acute respiratory infections, diseases of the musculoskeletal system, respiratory diseases, infections and skin diseases, etc.